2023
DOI: 10.3389/fpls.2022.1099362
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane mosaic virus orchestrates the lactate fermentation pathway to support its successful infection

Abstract: Viruses often establish their own infection by altering host metabolism. How viruses co-opt plant metabolism to support their successful infection remains an open question. Here, we used untargeted metabolomics to reveal that lactate accumulates immediately before and after robust sugarcane mosaic virus (SCMV) infection. Induction of lactate-involved anaerobic glycolysis is beneficial to SCMV infection. The enzyme activity and transcriptional levels of lactate dehydrogenase (LDH) were up-regulated by SCMV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Moreover, H 2 O 2 accumulation may lead to BaMV‐induced chlorotic symptoms (Lin et al., 2022 ). In addition, the manifestation of mosaic symptoms in SCMV‐infected maize leaves is accompanied by elevated levels of H 2 O 2 (Jiang et al., 2022 ). A recent report showed that ZmCATs could enhance SCMV replication by mitigating cellular oxidative damage caused by excessive H 2 O 2 (Tian et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, H 2 O 2 accumulation may lead to BaMV‐induced chlorotic symptoms (Lin et al., 2022 ). In addition, the manifestation of mosaic symptoms in SCMV‐infected maize leaves is accompanied by elevated levels of H 2 O 2 (Jiang et al., 2022 ). A recent report showed that ZmCATs could enhance SCMV replication by mitigating cellular oxidative damage caused by excessive H 2 O 2 (Tian et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HC-Pro could interfere with miRNA to function and increase miRNA accumulation (Kasschau et al, 2003), and the induction of both miRNAs and their targets by several potyviruses, such as SCMV or turnip mosaic virus, has been found (Cui et al, 2020;Xia et al, 2018) Moreover, H 2 O 2 accumulation may lead to BaMV-induced chlorotic symptoms (Lin et al, 2022). In addition, the manifestation of mosaic symptoms in SCMV-infected maize leaves is accompanied by elevated levels of H 2 O 2 (Jiang et al, 2022). A recent report showed that ZmCATs could enhance SCMV replication by mitigating cellular oxidative damage caused by excessive H 2 O 2 (Tian et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 6K2-induced vesicles could also move from cell to cell during TuMV infection [49]. The 6K2 of the sugarcane mosaic virus could interact with lactate dehydrogenase to support virus infection [50]. addition to its functions related to viral pathogenicity, TuMV 6K2 could serve as an elicitor for the unfolded protein response (UPR) and upregulate the selective autophagy receptor gene NBR1 in a UPR-dependent manner [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has demonstrated that the manifestation of mosaic symptoms in SCMV‐infected maize leaves is accompanied by elevated levels of H 2 O 2 (Jiang, Du, Wang, et al., 2023 ). Therefore, we hypothesized that catalases could respond to SCMV infection as a protective mechanism against oxidative stress‐induced cell damage.…”
Section: Introductionmentioning
confidence: 99%